Seminar Smart Parenting di Era Digital - Aisa, Aufia; Rahmawati, Rina Dian; Shofiyani, Amrini; Subhan, Muhammad; Lestari, Evi Endha; Umami, Fahmi Najah; Jannah, Ummi Nur (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
The lack of understanding of the Gambiran Village community regarding smart parenting in forming children's character in the digital era is the basis for holding a